Comparative genomics of global optrA-carrying Enterococcus faecalis uncovers a common chromosomal hotspot for optrA acquisition within a diversity of core and accessory genomes. Issue 6 (9th June 2020) - Freitas, Ana R.; Tedim, Ana P.; Novais, Carla; Lanza, Val F.; Peixe, Luísa
Abstract : Linezolid-resistant Enterococcus faecalis (LREfs) carrying optrA are increasingly reported globally from multiple sources, but we lack a comprehensive analysis of human and animal optrA -LREfs strains. To assess if optrA is dispersed in isolates with varied genetic backgrounds or with common genetic features, we investigated the phylogenetic structure, genetic content [antimicrobial resistance (AMR), virulence, prophages, plasmidome] and optrA -containing platforms of 27 publicly available optrA -positive E. faecalis genomes from different hosts in seven countries. At the genome-level analysis, an in-house database with 64 virulence genes was tested for the first time. Our analysis showed a diversity of clones and adaptive gene sequences related to a wide range of genera from Firmicutes . Phylogenies of core and accessory genomes were not congruent, and at least PAI-associated and prophage genes contribute to such differences. Epidemiologically unrelated clones (ST21, ST476-like and ST489) obtained from human clinical and animal hosts in different continents over eight years (2010–2017) could be phylogenetically related (3–126 SNPs difference). optrA was located on the chromosome within a Tn 6674 -like element ( n =10) or on medium-size plasmids (30–60 kb; n =14) belonging to main plasmid families (RepA_N/Inc18/Rep_3). In most cases, the immediate gene vicinity of optrA was generally identical in chromosomal (Tn 6674 ) or plasmid ( impB-fexA-optrA ) backbones. Tn 6674 was always inserted into the same ∆ radC integration site and embedded in a 32 kb chromosomal platform common to strains from different origins (patients, healthy humans, and animals) in Europe, Africa, and Asia during 2012–2017. This platform is conserved among hundreds of E. faecalis genomes and proposed as a chromosomal hotspot for optrA integration. The finding of optrA in strains sharing common adaptive features and genetic backgrounds across different hosts and countries suggests the occurrence of common and independent genetic events occurring in distant regions and might explain the easy de novo generation of optrA -positive strains. It also anticipates a dramatic increase of optrA carriage and spread with a serious impact on the efficacy of linezolid for the treatment of Gram-positive infections.